The study on sources and application of funds of ERLSB from July 2008 to June 2009 / Nazehan Abdullah Sani - Abdullah Sani, Nazehan (Faculty of Business and Management, 2010)
This paper study on the Sources and Application of Funds of Express Rail Link Sdn. Bhd. This study will focus on the company monthly cash flow from July 2008 to June 2009. A rough idea on the cash position of a company can be obtain by looking at its company cash flow statement. However, there is a need for reliable information in which every party can use for better decision making and to enhance the understanding over an organization’s actual business performance, and not just based on assumptions or an idea over a particular situation. For this reason, researcher will conduct a thorough cash flow analysis to analyze the cash flow statement that meet the organization’s goals, to identify the limitation in gained and utilized the funds that affect the profitability of the company.